VOLUME KEMBANG ADONAN DAN SENSORY ROTI MANIS YANG DIBUAT DARI MODIFIED TALIPUK FLOUR (MOTAF) [Dought Volume and Sensory Properties of Sweet Bread made from Modified Talipuk Flour (Motaf)] - Ema Lestari; Dwi Sandri; Fatimah Fatimah; Umaira Umaira (Jurnal Teknologi & Industri Hasil Pertanian, 2019)
Modified talipuk flour (motaf) can reduce the amount of wheat flour utilization as the main ingredient in making sweet bread. This study was aimed to determine the dough volume and organoleptic properties of sweet bread made from modified talipuk flour (motaf) with 6 formulations namely 0%, 5%, 10%, 15%, 20% and 25% (w/w). The hedonic sensory test was applied to 30 panelists. The results showed that the addition of motaf increased the taste and aroma scores, but decreased the volume of dough development, color score, texture, and overall acceptance of sweet bread. The highest volume of dough development was 57.17 cm found in the 5% formulation of motaf.